2021
DOI: 10.1155/2021/6624101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effects of Valproate and Oxcarbazepine on Sexual Function, Sperm Quality, and Sex Hormones in Males with Epilepsy

Abstract: Aims. Although several studies have indicated that valproate (VPA) and oxcarbazepine (OXC) cause reproductive endocrine disorders and sexual dysfunction, there remains some controversy regarding these issues in males with epilepsy. This study is aimed at evaluating the effects of VPA and OXC on sexual function, sperm quality, and sex hormones in young males with epilepsy. Methods. Males with newly diagnosed epilepsy treated with VPA and OXC were recruited, and sexual function questionnaires (International Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In comparison with non-epileptic men, those affected by epilepsy have been reported to have a higher likelihood of fertility issues; this is possibly associated with the sexual dysfunction issues, which have been reported in up to 71% of these patients [45]. Guo et al [46] prospectively evaluated the sperm quality of 44 young males with epilepsy (e.g., 23 being treated with valproic acid and 21 receiving oxcarbamazepine) and 30 age-matched healthy individuals. The sperm parameters were significantly reduced in those patients on valproic acid vs. both healthy individuals and those on carbamazepine.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with non-epileptic men, those affected by epilepsy have been reported to have a higher likelihood of fertility issues; this is possibly associated with the sexual dysfunction issues, which have been reported in up to 71% of these patients [45]. Guo et al [46] prospectively evaluated the sperm quality of 44 young males with epilepsy (e.g., 23 being treated with valproic acid and 21 receiving oxcarbamazepine) and 30 age-matched healthy individuals. The sperm parameters were significantly reduced in those patients on valproic acid vs. both healthy individuals and those on carbamazepine.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding valproic acid, research has found that the decreased expression of phosphorylated protein and Ki67 in the testis may affect the formation of the acrosome during sperm generation, leading to premature acrosome reactions and abnormal sperm heads. In clinical studies, the novel AED oxcarbazepine has been shown to increase sperm motility, concentration, and vitality ( Guo et al, 2021 ; Wu et al, 2018 ). The authors speculate that this may have a positive effect on sperm production and maturation by raising FSH and LH levels.…”
Section: Main Textmentioning
confidence: 99%
“…[6][7][8] Moreover, in men, VPA can have detrimental effects on sperm quality and testicular function/volume and may cause infertility. 9,10 Although the prognosis for IGE is more favorable than for some other epilepsies, up to 15% of individuals with IGE remain refractory to treatment. 5,11 The ASM perampanel (PER) acts as a noncompetitive antagonist of the αamino-3-hydroxy-5-methyl-4isoxazolepropionic acid receptor, 12,13 and it is widely approved for the treatment of focal onset seizures and the treatment of GTCS in people with IGE.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of VPA in women of childbearing age is limited due to its teratogenic effects, and its negative neurodevelopmental effects on in utero exposed children 6–8 . Moreover, in men, VPA can have detrimental effects on sperm quality and testicular function/volume and may cause infertility 9,10 . Although the prognosis for IGE is more favorable than for some other epilepsies, up to 15% of individuals with IGE remain refractory to treatment 5,11 …”
Section: Introductionmentioning
confidence: 99%